A participação da sociedade no procedimento de edição dos precedentes trabalhistas qualificados - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
The research is dedicated to the study of binding precedents and their integration into the practice of the labor judicial process, focusing on the need to implement social participation in the procedure preceding its issuance. The issue of access to justice is examined based on the theory of the renewal waves of justice, which in current times is manifested in the provisions of Law no 13.105/2015 – New Code of Civil Procedure, bringing propositions that require a re- reading of the jurisdiction system. It outlines the importance of establishing interaction instruments between society and the Superior Labor Court, using structural process techniques, to democratize the process of constructing binding decisions, aiming to meet the constitutional command of access to justice in its broad conception. It is proposed, through the amendment of the TST's internal regulations, the incorporation of a procedure of deliberative public hearings where the opinions and opinions of society are valued, on the premise of giving them responsibility for constructing negotiated solutions and establishing theses for controversies in repetitive demands. The study was carried out using the deductive-empirical method, with a translational research approach to expose the propositions.
Keywords: Precedente vinculante; Acesso à justiça; Participação social; Processo do Trabalho; Binding precedent; Access to justice; Social participation; Work process; CNPQ::CIENCIAS SOCIAIS APLICADAS::DIREITO